La Vivencia a San Basilio De Palenque 2015 Festival de Tambores y Expresiones Culturales “un Recorrido Por La Historia Cultural y Ancestral Palenquera” (2019)
This degree work includes the collection, organization and analysis of information obtained by the seedbed of research Sowing of the University Antonio Nariño on the experience of San Basilio de Palenque from 8 to 13 October 2015, planned and executed by students of sixth semester in the dance subject of the Atlantic coast belonging to the Bachelor in Art Education with Emphasis in Dance and Theater program.